#TITLE_ALTERNATIVE# - ABIDIN M. (NIM 20105319); Pembimbing : Dr. Oki Neswan dan Dr. Moedji Raharto, ZAINAL
Direction of kiblah can be determined by using spherical trigonometric theorems. The geographical coordinate of position of Ka'ba is 39o50′ longitude and +21o25' latitude or more precisely 39o50′34′′ longitude and +21o25′21′′ latitude. This geographical coordinates represent the position of Mecca. We need a more accurate coordinates to represent the position of Kibla. For the purpose of this study, if suffices to use the coordinate of Mecca. In practice, most people determine direction of kibla using rough estimate of direction. This thesis will discuss the influence of error on the determination of kibla direction and its on geographical position of kibla that calculated by position initially (km).